2002
DOI: 10.1046/j.1469-0705.2002.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Placenta accreta diagnosed at 9 weeks' gestation

Abstract: The majority of cases of placenta accreta are unanticipated and initially identified intraoperatively. Although color Doppler ultrasound is adequate for the evaluation of placenta accreta in the third trimester, ultrasound diagnosis in the first trimester has never been reported. To our knowledge, this is the first case of placenta accreta detected at 9 weeks' gestation by ultrasound. Placenta accreta with intraplacental lacunae can be identified together with a loss of the hypoechogenic retroplacental myometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 12 publications
2
36
0
3
Order By: Relevance
“…According to literature the earliest gestation at which placenta accreta has been diagnosed by ultrasound is 9 weeks in a case of scar pregnancy. The woman continued pregnancy and underwent emergency cesarean hysterectomy at 37 weeks because of placenta increta [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature the earliest gestation at which placenta accreta has been diagnosed by ultrasound is 9 weeks in a case of scar pregnancy. The woman continued pregnancy and underwent emergency cesarean hysterectomy at 37 weeks because of placenta increta [11].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In contrast to these studies, a prospective study of 1294 cases demonstrated an association with small-for-gestational age infants among 13 patients with large placental sonolucencies (defined as 95 cm in longest diameter) in the second trimester. 6,12 In addition, Cooley et al 13 found that placental sonolucencies in the second trimester were more common among patients who had presented with threatened abortion in the first trimester. 13 Because of the small number of cases of spontaneous abortion in our cohort (4 cases), a clinically useful statistical analysis could not be performed.…”
Section: Discussionmentioning
confidence: 97%
“…6,10 The incidence of second-and third-trimester placental sonolucencies, defined with varying size and number thresholds, ranges from 2.2% to 17.8%. 1Y3 In this study, it was found that first-trimester placental sonolucencies 0.7 cm or greater were quite common in the general obstetric population, seen in almost 1 in 4 sonographic studies (22.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Néanmoins, Esmans et al ont rapporté le cas d'un placenta percreta responsable d'une rupture utérine à la fin du premier trimestre de la grossesse sur un utérus sain [18]. Pour tous ces cas, le diagnostic a été fait rétrospectivement, à la suite d'hémorragies spontanées ou provoquées, nécessitant dans la plupart des cas une hystérectomie [19][20][21]. L'examen de la pièce opératoire a mis en évidence des agrégats multifocaux de trophoblaste ainsi que des villosités choriales pénétrant le myomètre et pouvant atteindre la séreuse utérine [20].…”
Section: Discussionunclassified